2009
DOI: 10.1063/1.3270190
|View full text |Cite
|
Sign up to set email alerts
|

A benchmark theoretical study of the electronic ground state and of the singlet-triplet split of benzene and linear acenes

Abstract: A benchmark theoretical study of the electronic ground state and of the vertical and adiabatic singlet-triplet ͑ST͒ excitation energies of benzene ͑n =1͒ and n-acenes ͑C 4n+2 H 2n+4 ͒ ranging from naphthalene ͑n =2͒ to heptacene ͑n =7͒ is presented, on the ground of single-and multireference calculations based on restricted or unrestricted zero-order wave functions. High-level and large scale treatments of electronic correlation in the ground state are found to be necessary for compensating giant but unphysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
216
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(247 citation statements)
references
References 167 publications
(95 reference statements)
22
216
1
3
Order By: Relevance
“…With B3LYP, the least stable isomer (1) is identified as a singlet biradical (<S 2 > = 0.76), consistent with the earlier study of Bendikov et al [71], although it should be noted that a recent benchmark theoretical study, including a focal point analysis applied onto the results of a series of symmetryrestricted electron correlated calculations of gradually increased sophistication, revealed that 1 has a 1 A g closed-shell singlet ground state [72]. Tetrabenzanthracene (6), having the maximum number of -sextets (five) among the selected heptabenzenoids, is the isomer with the highest thermodynamic stability according to our calculations.…”
Section: Heptabenzenoidssupporting
confidence: 69%
“…With B3LYP, the least stable isomer (1) is identified as a singlet biradical (<S 2 > = 0.76), consistent with the earlier study of Bendikov et al [71], although it should be noted that a recent benchmark theoretical study, including a focal point analysis applied onto the results of a series of symmetryrestricted electron correlated calculations of gradually increased sophistication, revealed that 1 has a 1 A g closed-shell singlet ground state [72]. Tetrabenzanthracene (6), having the maximum number of -sextets (five) among the selected heptabenzenoids, is the isomer with the highest thermodynamic stability according to our calculations.…”
Section: Heptabenzenoidssupporting
confidence: 69%
“…Therefore, the broken-symmetry determinant of UDFT contains limited information of the entire many-electron wave function, and it may not describe the nature of the ground state. In the past 10 y, some accurate but relatively inexpensive theories have been developed and applied to higher acenes (49)(50)(51)(52)(53)(54)(55)(56)(57). Among them, the most widely accepted one seems to be the density matrix renormalization group method in combination with the complete active-space configuration interaction theory (49).…”
Section: Significancementioning
confidence: 99%
“…Consequently, the experimental singlet-triplet energy gaps (ST gaps) of n-acenes are only available up to pentacene [109][110][111][112]. On the theoretical side, since n-acenes belong to conjugated π-orbital systems, high-level ab initio multi-reference methods, such as the density matrix renormalization group (DMRG) algorithm [115,122], the variational twoelectron reduced density matrix (2-RDM) method [121,124], and other high-level methods [114,[118][119][120], are typically required to capture the essential strong static correlation effects.…”
Section: Electronic Properties Of Linear Acenesmentioning
confidence: 99%
“…Recently, linear n-acenes (C 4n+2 H 2n+4 ), containing n linearly fused benzene rings (see Figure 10), have attracted considerable interest in the research community owing to their promising electronic properties [20,21,[45][46][47][48][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124]. The electronic properties of nacenes have been found to be highly dependent on the chain lengths.…”
Section: Electronic Properties Of Linear Acenesmentioning
confidence: 99%